Self-reliance of Tribal through Corporate Social Responsibility (CSR): A Case Study in Tripura - Uchoi, Oliver; Singh, Ram (Indian Journal of Extension Education, 2020)
Corporate Social Responsibility (CSR) is the most important global issue with serious challenges and implications on almost all the sectors of the society. Emerging economies of the world including India are coping with the issues relating to poverty, hunger, malnutrition, women rights, child labour, farmers suicide and community welfare etc. Therefore, corporate sector has its vital role to address these societal issues through CSR. The paper is an effort to document the socio-economic improvements of tribal farmers in the state of Tripura through CSR. A sample of 120 beneficiaries of CSR of Tripura Forest Development & Plantation Corporation Limited (TFDPC) in five adopted villages under TFDPC was taken. It was found that CSR of TFDPC in study area impacted a lot for upliftment of livelihood and income of tribal of the state. Hence, the intervention of CSR including all organizations must be tapped for development the remote areas of the country, especially the remotely located tribes of hilly areas.
Keywords: CSR; Rubber and Tribe; TFDPC; Tripura